(untitled) (Bangladesh Journal of Medical Science, 2024)
Background: Pityriasis Versicolor (PV) is a chronic superficial fungal infection of skin caused by lipophilic yeast Malassezia species. Its prevalence, predisposing factors and clinical presentations varies in different geographical locations around the world. Despite being a common disease, its diagnosis and treatment remain a challenge. The aim of this study was to document the clinico-epidemiological characteristics of the participants diagnosed with PV. Materials and Methods: A descriptive crosssectional study was carried out on 104 consecutive participants attending the Outpatient Department of National Research Institute of Unani Medicine for Skin Disorders, Hyderabad during 1st July, 2020 and 31stJuly, 2021. Their demographic data, risk factors, clinical features, and temperament were recorded in the case record form. The participants were diagnosed clinically and confirmed by direct microscopy. The data were analysed retrospectively. Results: In this study, 75 participants (72%) were males and the ratio of male to female was 2.6:1. The most frequently affected participants were in 20–40 years of age group. The mean age was 29.14 (±10.52) years. PV was present in 28.8% students, 21.15% workers, 31.7% employees, 11.5% housewives and 6.7% businessmen. The most common affected site was back followed by neck and chest. PV was found prone to the Fitzpatrick skin types 4 (49.03%) and 3 (27.8%). Hypo-pigmented lesions were more common.The Malassezia species was present in multiple lesions of all the participants. Conclusions: This study documented the clinico-epidemiological profile of PV. The findings of this study may provide us current understanding of PV in India. Bangladesh Journal of Medical Science Vol. 23 No. 01 January’24 Page : 141-149